Perencanaan Perawatan Pada Unit Kompresor Tipe Screw Dengan Metode RCM di Industri Otomotif - Susanto, Agustinus Dwi; Azwir, Hery Hamdi (Universitas Muhammadiyah Surakarta, 2018)
Production process at PT. Showa Indonesia Manufacturing is not always smooth, due to the ignorance of the reliability of the machine. Breakdown can occur at any time and cause uncertainty of the availability of machinery in the production process, causing considerable losses to the company. This study was conducted on a compressor machine used to produce the pressurized air that used to run the production machinery. Based on the research, the highest damage level is on the compressor machine 4, 8, 10, 5, 16, and 6 with total damage of 70.1%. This is due to the complex machine system and the less optimal maintenance system. Reliability Centered Maintenance (RCM) method is used to analyze the system to identify components that fall within the critical category. The results of the analysis, obtained some critical components which required optimal replacement interval by minimizing downtime. Further planning activities on each critical component is based on FMEA and RCM Decision Worksheet. With the application of RCM method, total downtime decreased by 44.59% from previous preventive actions.Â